Coronary angiography with or without percutaneous coronary intervention in patients with hemophilia—Systematic review. Issue 1 (12th September 2017) - Boehnel, Christian; Rickli, Hans; Graf, Lukas; Maeder, Micha T.
Abstract: Objectives: We aimed to summarize the evidence for periprocedural and long‐term strategies to both minimize the bleeding risk and ensure sufficient anticoagulation and antiaggregation in hemophilia patients undergoing coronary angiography with or without percutaneous coronary interventions (PCI). Background: Hemophilia patients undergoing coronary angiography and PCI are at risk of bleeding due to deficiency of the essential clotting factors VIII or IX combined with the need of peri‐interventional anticoagulation and antiaggregation and dual antiplatelet therapy (DAPT) after PCI. Methods: We report on a patient with moderate hemophilia B undergoing single‐vessel PCI with administration of factor IX concentrate during the procedure and during the 1‐month DAPT period. In addition, a systematic review of patients ( n = 54, mean age 58 ± 10 years) with hemophilia A ( n = 45, 83%) or B ( n = 9, 17%) undergoing coronary angiography with or without PCI is presented. Results: Peri‐interventional factor substitution was performed in the majority (42 of 54, 78%) but not all patients. In 38 of 54 (70%) patients undergoing coronary angiography, PCI with balloon dilation ( n = 5), bare metal ( n = 31), or drug‐eluting stents ( n = 2) was performed. For PCI unfractioned heparin ( n = 24), low molecular weight heparin ( n = 2), bivalirudin ( n = 4), or no periprocedural anticoagulation at all ( n = 8) were used. PCI was successful in all cases. After stenting, the majority (28 of 33; 85%) was treated with DAPT (median duration 1 month). Major periprocedural bleeding episodes occurred in 3 of 54 (6%) patients. Bleeding during follow‐up occurred in 11 of 54 (20%) patients. Conclusions: Coronary angiography and PCI in patients with hemophilia are effective and safe when applying individualized measures to prevent bleeding.